Managing Cross Culture Diversity: Issues and Challenges in Workplace - Siti Maharani; Umar Mono; Alemina Br Perangin-Angin (CV Wahana Publikasi, 2022)
This study is focused on describing the horizontal communication among employees with ethnic country diversity in the communication process and examining the barriers to communication as well as efforts made by the employees in resolving horizontal communication conflicts. The data collection technique used is a focus group discussion of structured interviews with three Indonesian and three Foreign employees. The interviews were done by dividing the employees into two discussion groups according to their ethnicity to answer the same research questions. The results show that the horizontal communication process between employees is going well and needs to be influenced by the diversity of employees in terms of ethnicity. Barriers to horizontal communication between employees are communication barriers in terms of employee psychology and semantics. Efforts made by employees in overcoming horizontal communication conflicts are by compromising. However, Indonesian employees tend to make efforts to integrate the implications of this study following the results of the research, which stated that employees’ ethnic diversity did not directly affect the continuity of horizontal communication among employees in the company.